2002
DOI: 10.1017/s1446788700003542
|View full text |Cite
|
Sign up to set email alerts
|

A problem on rough parametric Marcinkiewicz functions

Abstract: In this note the authors give the L 2 (R") boundedness of a class of parametric Marcinkiewicz integral H P aA with kernel function ft in Z. log + L(5""') and radial function h(\x |) 6 /°°(L«)(R + )forl < q < oo. As its corollary, the Z/(R")(2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 8 publications
2
46
0
Order By: Relevance
“…However, the authors of [14] showed that M ρ Ω,1 is still bounded on L p (R n ) for 1 < p < ∞ when Re(ρ) > 0 and Ω ∈ Lip α (S n−1 ) with 0 < α ≤ 1. These results were improved in [11]. In fact, the authors proved…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the authors of [14] showed that M ρ Ω,1 is still bounded on L p (R n ) for 1 < p < ∞ when Re(ρ) > 0 and Ω ∈ Lip α (S n−1 ) with 0 < α ≤ 1. These results were improved in [11]. In fact, the authors proved…”
Section: Introductionmentioning
confidence: 87%
“…f L p (R m ) (11) holds for |1/p − 1/2| < 1/γ ′ . Consequently, by (9) and (12), we finish the prrof of Theorem 1.…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…For example, see [5,23,24,27] for the case ̺ ≡ 1, [4,17] for the case ̺ > 0, [12,21] for the case ̺ ∈ C with Re̺ > 0. On the other hand, the investigation of the parametric Marcinkiewicz integral operators µ ̺ Ω,h,Φ with rough kernels on the unit sphere as well as in the radial direction have also received a large amount of attention of many authors (see [2,9,10,11,13] et al). In particular, Al-Qassem and Pan [2] obtained the following result.…”
Section: Introductionmentioning
confidence: 99%
“…Reasoning as above, (3.32), (3.37), (3.39) and Lemma 3.3 provide 8). By using this argument repeatedly we ultimately obtain that…”
Section: Lemma 39mentioning
confidence: 66%
“…An improvement of the result in [14] in the case p = 2 was obtained in [8] as described in the following theorem:…”
Section: H(t)| (Log(2 + |H(t)|))mentioning
confidence: 94%